MITIGATING CONSTRUCTION FAULTS IN COASTAL APARTMENT BUILDINGS: A CASE STUDY OF APARTMENTS OF, KARACHI CITY, PAKISTAN - Uroosa Solangi,; Abdul Waheed Memon,; Dr. Saima Kalwar, (Spectrum of Engineering Sciences, 2025)
Karachi is largest city of Pakistan, and it is experiencing rapid urbanization and apartments demand, particularly along its coastal. However, apartment buildings in these areas face significant challenges due to harsh environmental conditions such as high humidity, saline air, and extreme weather. This study investigates the common exterior and interior construction faults in coastal Apartments, located near Karachi’s Seaview coastline. Using multi-method techniques including, resident and expert questionnaires, field surveys, the research identifies common construction issues such as water seepage, rusting, plaster cracks, and poor interior finishes. Results reveal that the primary causes include substandard material use, lack of waterproofing, and poor workmanship, all exacerbated by Karachi’s coastal environment. The study proposes strategic solutions including the use of corrosion-resistant materials, enhanced construction supervision, and climate-adaptive design methods. These recommendations aim to improve construction quality, reduce long-term maintenance costs, and ensure safer, more durable coastal housing in Karachi and other coastal areas.